INFLUENCE OF WHEAT AND CORN YIELD AND PRICE PARITY FROM THE CURRENT YEAR ON FOLLOWING YEAR SOWING STRUCTURE - Novković, Nebojša; Mutavdžić, Beba; Vukelić, Nataša; Tekić, Dragana; Novakovic, Tihomir; Šarac, Veljko; Nikolić, Srboljub (Journal on Processing and Energy in Agriculture, 2023)
The subject of this research are the production characteristics and price parity of wheat and corn in the Republic of Serbia. The aim of this research is to determine whether there is a relationship between the yield and price parity from the current year and the sowing structure of these two crops in the following year. The analysis was performed for the period 2011-2021.Statistical processing was performed using descriptive statistical analysis and multiple linear regression. Research results determined that the average area under wheat was about 600 thousand hectares, while the average area under corn was about 400 thousand hectares than the area under wheat. The yield of wheat in the observed period was relatively stable, while the yield of corn showed significant variations. The average production of corn was about 3.6 milion tons, i.e. it was 2.3 times higher than the average wheat production. Price parity of wheat and corn averaged 1.12. Regression models resuts determined a statistically significant influence of the yield and price parity of wheat and corn from the current year on the areas under wheat and corn in the following year.
Keywords: wheat, corn, sowing structure, yield, price parity, Republic of Serbia